Immunophenotypic Profiles in Polycystic Ovary Syndrome - Cong Hu; Bo Pang; Zhanchuan Ma; Huanfa Yi (Hindawi Limited, 2020)
Polycystic ovary syndrome (PCOS) a long-known endocrinopathy and one of the most common endocrine-reproductive-metabolic disorders in women, which can lead to infertility. Although the precise etiology remains unclear, PCOS is considered as a complex genetic trait, with a high degree of heterogeneity. Besides, hormones and immune cells, including both innate and adaptive immune cells, are reportedly a cross talk in PCOS. Chronic low-grade inflammation increases autoimmune disease risk. This proinflammatory condition may, in turn, affect vital physiological processes that ultimately cause infertility, such as ovulation failure and embryo implantation. Here, we review the accumulating evidence linking PCOS with inflammatory status providing an overview of the underlying hormone-mediated dysregulation of immune cells. We mainly focus on the correlational evidence of associations between immune status in women and the increased prevalence of PCOS, along with the specific changes in immune responses. Further recognition and exploration of these interactions may help elucidate PCOS pathophysiology and highlight targets for its treatment and prevention.